Integrity Moderates the Relationship between Work Experience and Tax Inspector Performance at the Intermediate Tax Service Office Within the Regional Office of the Directorate General of Taxes of Central Java I - Qosidah, Nanik; Husnurrosyidah, Husnurrosyidah (Global Health Science Group, 2022)
The purpose of the study is toanalyze the effect of work experience on the performance of tax inspectors. Analyzing the integrity of moderating work experience to the performance of tax inspectors. The research design used Multiple Regression Analysis (MRA). The research sample was a tax inspector at the Associate Tax Service Office in the Regional Office of the Directorate General of Taxes of Central Jaw I, which totaled 60 respondents. The results of the study explained that work experience contributes to improving the performance of tax inspectors, integrity strengthens the relationship between work experience and tax inspector performance.